2007
DOI: 10.1515/znc-2007-9-1006
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Molluscicidal Investigations of Fagonia arabica

Abstract: The aqueous methanolic extract of the aerial parts of Fagonia arabica L. (family Zygophyllaceae) was successively fractionated using certain organic solvents. From the ethyl acetate fraction, two flavonoid glycosides were isolated and identified as kaempferol-7-O-rhamnoside and acacetin-7-O-rhamnoside. Four triterpenoidal glycosides were isolated from the butanolic layer. Their structures were elucidated on the basis of the spectral and chemical data as 3-O-β-D-glucopyranosyl-(1→3)-α-L-arabinopyranoside oleano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 13 publications
1
38
0
Order By: Relevance
“…It was suggested that metabolites of quercetin glucosides accumulate in the aorta -a target site for its anti-atherosclerotic effect, and attenuate lipid peroxidation that occur in the Extract of Achillea fragrantissima Downregulates ROS Production and Protects Astrocytes from Oxidative-Stress-Induced Cell Death 447 aorta, along with the attenuation of hyperlipidemia (Kamada et al, 2005;Terao, 1999;Terao et al, 2008). Two other compounds in the Af extract were also identified by LC-MS: acacetin 7-o-rhamnoside, which was also identified in the aerial parts of several plants (El-Wakil, 2007;Sharaf et al, 1997), and acacetin 7-o-glucoside, which was also found in the antiinflammatory extract of Mcfadyena unguis-cati L. (Aboutabl et al, 2008 (Iriti et al, 2010). Substances that can restrict and/or protect brain cells from oxidative stress show promise as potential tools in the therapy of various brain injuries and neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 94%
“…It was suggested that metabolites of quercetin glucosides accumulate in the aorta -a target site for its anti-atherosclerotic effect, and attenuate lipid peroxidation that occur in the Extract of Achillea fragrantissima Downregulates ROS Production and Protects Astrocytes from Oxidative-Stress-Induced Cell Death 447 aorta, along with the attenuation of hyperlipidemia (Kamada et al, 2005;Terao, 1999;Terao et al, 2008). Two other compounds in the Af extract were also identified by LC-MS: acacetin 7-o-rhamnoside, which was also identified in the aerial parts of several plants (El-Wakil, 2007;Sharaf et al, 1997), and acacetin 7-o-glucoside, which was also found in the antiinflammatory extract of Mcfadyena unguis-cati L. (Aboutabl et al, 2008 (Iriti et al, 2010). Substances that can restrict and/or protect brain cells from oxidative stress show promise as potential tools in the therapy of various brain injuries and neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, the reaction conditions are harsh, and the post‐treatment is relatively complicated. The other one is to directly synthesize macromolecular antioxidants with the reactive monomers containing antioxidative groups or chemically graft antioxidative groups onto organic backbones with high molecular weight . Beer et al .…”
Section: Introductionmentioning
confidence: 99%
“…The other one is to directly synthesize macromolecular antioxidants with the reactive monomers containing antioxidative groups or chemically graft antioxidative groups onto organic backbones with high molecular weight. [16][17][18][19][20] Beer et al firstly synthesized a,x-diene monomers bearing one alcohol functionality from 10-undecenoic acid, and then reacted with 3,5-di-tert-butyl-4-hydroxy-cinnamic acid or 3-(3,5-di-tert-4-hydroxyphenyl) propanoic acid to prepare hindered phenolic macromolecular antioxidants for enhanced long-term stabilization of polyolefin. 21 In our previous work, we synthesized a star-shaped macromolecular antioxidant by grafting 2,6-di-tert-butyl-4-hydroxy methyl phenol onto per-2,3-acetyl-bcyclodextrin with isophorone diisocyanate as linkage.…”
Section: Introductionmentioning
confidence: 99%
“…Due to low thermal stability, poor migration resistance and poor extraction resistance, the physical loss of low molecular weight antioxidant was large during polymer processing and long‐term service, which severely restricted its applications. In order to overcome the problem, macromolecular antioxidant had attracted much attention in recent years . For example, Kim synthesized several kinds of polymeric antioxidants by copolymerization or homopolymerization of functional monomers containing hindered phenol.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] For example, synthesized several kinds of polymeric antioxidants by copolymerization or homopolymerization of functional monomers containing hindered phenol. El-Wakil et al [9][10][11][12] studied the grafting of o-aminophenol, 1,2-phenylenediamine,1,5-diaminonaphthalene, and N-(4-aminodiphenyl methane) acrylamide onto natural rubber. Podesva 13,14 synthesized a polymer-bound antioxidant by free radical addition reaction between a hindered phenolic antioxidant with a sulfanyl group and hydroxylterminated polybutadiene.…”
Section: Introductionmentioning
confidence: 99%